Implementasi Kemitraan dalam Pemolisian Komunitas untuk Pencegahan Praktik Destructive Fishing (Studi Kasus Perairan Laut Maluku Utara) - Septiani Kusherawati (Jurnal Kriminologi Indonesia, 2016)
This study focuses on the issue of partnership implementation on community policing which is faced by Directorate Marine Police of Maluku Utara (Ditpolairda Maluku Utara) with community and other agencies in order to prevent destructive fishing. The discussion of this issue is analyzed by social exchange theory and integrated crime prevention. The author uses qualitative approach with descriptive purpose. The result shows that partnership encounters several problems which are associated with self-interest issue and the lack of personnel, facilities, and infrastructure. Therefore, every agent in partnership should be integrated to form an effective and efficient destructive fishing prevention.